2018
DOI: 10.1016/j.bbamcr.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

IKK1/2 protect human cells from TNF-mediated RIPK1-dependent apoptosis in an NF-κB-independent manner

Abstract: TNF signaling is directly linked to cancer development and progression. A broad range of tumor cells is able to evade cell death induced by TNF impairing the potential anti-cancer value of TNF in therapy. Although sensitizing cells to TNF-induced death therefore has great clinical implications, detailed mechanistic insights into TNF-mediated human cell death still remain unknown. Here, we analyzed human cells by applying CRISPR/Cas9n to generate cells deficient of IKK1, IKK2, IKK1/2 and RELA. Despite stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Constitutive IKK2 activation in intestinal epithelial cells was further demonstrated to induce intestinal tumors in mice [ 43 ]. These findings are in accordance with the profound overexpression of IKK2 observed in cancers of the large intestine ( Table 2 ) [ 38 ]. On the functional level, IKK2 was shown to directly promote the development of lung cancer in an inflammation-dependent manner triggered by tobacco smoke, which was abrogated by ablation of IKK2 in myeloid cells [ 44 ].…”
Section: Activity Of Distinct Nf-κb Upstream Kinases In Cancersupporting
confidence: 88%
See 2 more Smart Citations
“…Constitutive IKK2 activation in intestinal epithelial cells was further demonstrated to induce intestinal tumors in mice [ 43 ]. These findings are in accordance with the profound overexpression of IKK2 observed in cancers of the large intestine ( Table 2 ) [ 38 ]. On the functional level, IKK2 was shown to directly promote the development of lung cancer in an inflammation-dependent manner triggered by tobacco smoke, which was abrogated by ablation of IKK2 in myeloid cells [ 44 ].…”
Section: Activity Of Distinct Nf-κb Upstream Kinases In Cancersupporting
confidence: 88%
“…To investigate the role of the upstream regulators of NF-κB-signaling IKK1 and IKK2 in human cancers, we applied database mining using COSMIC to determine their levels of overexpression ( Table 2 ) [ 37 , 38 ].…”
Section: Activity Of Distinct Nf-κb Upstream Kinases In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, this isoform-specific delineation of function has turned out to be overly simplistic. Increasingly, it appears that in certain human cell-types IKKα may play a substantial role, alongside IKKβ, in activation of canonical NF-κB signalling, both under physiological or pathological conditions [ 133 , 134 , 135 ] and as an adaptive response to inhibition of IKKβ [ 136 ]. The relative contribution of IKKα and IKKβ to disease-associated canonical NF-κB signalling should therefore be assessed prior to any decisions to apply IKKβ-, IKKα- or dual-selective inhibitors.…”
Section: Potential Reasons For the Lack Of Clinical Success Of Ikkmentioning
confidence: 99%
“…32,33 Moreover, it has been found that the activation of NF-κB suppresses caspase-8 activation through the induction of cIAP1 and cIAP2. 34,35 At this point, the Ras signaling pathway is connected to the anti-apoptosis pathway, which might be the major mechanism of fibrous epulis.…”
Section: Discussionmentioning
confidence: 99%